A wear-resistant and corrosion-resistant high-strength automobile sheet metal bracket

Through the combination of modified resin and inorganic filler, combined with electrostatic spraying technology, the problem of insufficient strength and wear resistance of automotive sheet metal bracket coating materials is solved, and a high-strength, wear-resistant and corrosion-resistant coating is achieved, which extends the Lifespan and improved stability.

CN118755350BActive Publication Date: 2024-12-27SUZHOU BAIDA PRECISION MACHINERY
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202410992903.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2024-06-13
Filing Date
2024-07-24
Publication Date
2024-12-27
Estimated Expiration
2044-07-24

AI Technical Summary

Technical Problem

The coating materials of existing automotive sheet metal brackets have problems such as low strength, poor wear resistance and corrosion resistance, resulting in a shortened service life.

Method used

Using a combination of modified resin and inorganic filler, an anti-corrosion coating is formed on the surface of the sheet metal bracket through electrostatic spraying technology. The coating is made of diethylene triamine propyl trimethoxysilane, polyurethane prepolymer, and epoxy resin. , and the modified inorganic filler and additive are composed of a high-strength, wear-resistant and corrosion-resistant coating after multi-step reaction and treatment.

Benefits of technology

The mechanical properties and wear resistance of sheet metal brackets are significantly improved, the service life is extended, and the stability and binding force of the coating are enhanced by the combination of dynamic covalent bonded curing agent and polydopamine solution modified inorganic filler.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004959349130000031
    Figure BDA0004959349130000031
  • Figure BDA0004959349130000032
    Figure BDA0004959349130000032
  • Figure BDA0004959349130000151
    Figure BDA0004959349130000151
Patent Text Reader

Abstract

The invention discloses a wear-resistant and corrosion-resistant high-strength automobile sheet metal bracket, which belongs to the technical field of sheet metal bracket processing and is used to solve the problem in the prior art that the strength, corrosion resistance and wear resistance of the automobile sheet metal bracket cannot be significantly improved after the metal surface of the automobile sheet metal bracket is coated with a wear-resistant and corrosion-resistant coating. The invention comprises a sheet metal bracket and a wear-resistant and corrosion-resistant coating coated on the outside of the sheet metal bracket, the wear-resistant and corrosion-resistant coating is obtained by spraying the wear-resistant and corrosion-resistant coating on the outside of the surface pretreated sheet metal bracket and curing and forming, the wear-resistant and corrosion-resistant coating is prepared from a composite modified resin, a small molecule curing agent, a modified inorganic filler and an auxiliary agent, and the invention prepares a wear-resistant and corrosion-resistant high-strength automobile sheet metal bracket by designing a composite of a soft segment and a hard segment of a polyurethane, a polyurethane prepolymer and an epoxy resin, and adding a small molecule curing agent with a dynamically reversible borate ester bond and a modified inorganic filler based on a metal foam.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sheet metal bracket processing, and in particular to a wear-resistant and corrosion-resistant high-strength automobile sheet metal bracket. Background Art

[0002] The automobile sheet metal bracket has one or more functions such as connectivity, load-bearing, reinforcement and positioning. It is also a structure formed by metal materials and certain specific forming processes. According to the needs of electrical professionals, after the battery layout position is determined, a sheet metal bracket needs to be designed for it to carry the battery and ensure that the bracket will not be damaged during the driving of the car. Therefore, the automobile sheet metal bracket has extremely high requirements for strength. In addition, in order to extend the service life of the automobile sheet metal bracket, it is necessary to improve the wear resistance and corrosion resistance of the automobile sheet metal bracket.

[0003] Patent application CN105925149A discloses a metal material, including a substrate and a protective coating disposed on the substrate. The raw material formula of the coating used in the protective coating includes the following components: UV monomer, polyurethane resin, modified polyurethane resin, photoinitiator, leveling agent, wetting agent, defoaming agent and ultraviolet absorber. The protective coating of the above metal material has good bending resistance and tensile resistance; however, the preparation method of the above coating does not involve a technical solution for improving the strength, wear resistance and corrosion resistance of the metal substrate.

[0004] Patent application CN103497552A discloses an anti-corrosion and wear-resistant coating, including tetraphenol ethane tetraglycidyl ether epoxy resin, aluminum nitride powder and inorganic filler, wherein the inorganic filler is gibbsite, attapulgite, carboxymethyl cellulose, etc.; however, the above-mentioned prior art does not modify the resin matrix and cannot significantly improve the corrosion resistance and mechanical properties of the resin itself. The above-mentioned resin material is easily shortened in service life after friction. In addition, the inorganic filler has poor adhesion to the resin matrix, which is not conducive to improving the overall stability of the coating material.

[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0006] The purpose of the present invention is to provide a wear-resistant and corrosion-resistant high-strength automobile sheet metal bracket, which is used to solve the technical problems in the prior art that the coating material sprayed on the sheet metal bracket has low strength and poor wear resistance and corrosion resistance.

[0007] The purpose of the present invention can be achieved by the following technical scheme: a wear-resistant and corrosion-resistant high-strength automobile sheet metal bracket, comprising a sheet metal bracket and a wear-resistant and anti-corrosion coating coated on the outside of the sheet metal bracket, wherein the wear-resistant and anti-corrosion coating is obtained by spraying the wear-resistant and anti-corrosion coating on the outside of the surface pre-treated sheet metal bracket and curing and forming;

[0008] The wear-resistant and anti-corrosion coating is obtained by processing the following steps:

[0009] S1, diethylenetriaminopropyltrimethoxysilane and deionized water are mixed and stirred to obtain a mixed solution; the mixed solution is heated to 100-110° C. and reacted until the volume of the mixed solution remains unchanged to obtain an organic liquid silanol;

[0010] S2, mixing organic liquid silanol, tannic acid and deionized water uniformly to obtain a mixed solution; heating the mixed solution to 110-120°C and reacting for 1-2h, using a vacuum pump to remove water during the reaction, then cooling the mixed solution to room temperature, and then dropping diisocyanate into the mixed solution. After the dropping is complete, heating it to 60-70°C, reacting for 30-60min, and then heating it to 80°C, reacting for 2-2.5h. After the reaction is completed, stopping heating to obtain a polyurethane prepolymer;

[0011] S3, according to weight parts, 30 parts of polyurethane prepolymer and 60-70 parts of epoxy resin are mixed uniformly to obtain a composite modified resin;

[0012] S4. Evenly mix the composite modified resin, small molecule curing agent, modified inorganic filler, leveling agent, dispersant and defoaming agent to obtain a mixture; the mixture is cured at 120-140° C. for 20-30 min, then melt-extruded, cooled, crushed and sieved to obtain a wear-resistant and anti-corrosion coating.

[0013] The wear-resistant and anti-corrosion coating prepared in the present invention is composed of a modified resin, a modified curing agent, a filler, a leveling agent, a dispersant and a defoaming agent. The above raw material components are blended, melt-extruded, cooled, crushed and sieved to obtain a wear-resistant and anti-corrosion coating with a certain particle size. The wear-resistant and anti-corrosion coating is then electrostatically sprayed. By controlling the corresponding process parameters and spraying thickness of the electrostatic spraying, a wear-resistant and corrosion-resistant high-strength sheet metal bracket is finally obtained.

[0014] Furthermore, in step S1, the dosage ratio of diethylenetriaminopropyltrimethoxysilane and deionized water is 25-35mL:100mL; the mixing speed is 100r / min, and the mixing time is 30-60min.

[0015] The reaction principle of diethylenetriaminopropyltrimethoxysilane is as follows:

[0016]

[0017] Furthermore, in step S2, the diisocyanate is any one of toluene diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, and p-phenylene diisocyanate, and a combination thereof; in step S3, the epoxy resin is bisphenol A epoxy resin.

[0018] Further, in step S4, the small molecule curing agent is prepared by the following steps:

[0019] Methanol and anhydrous magnesium sulfate are mixed evenly to obtain a mixed solid-liquid; 3-amino-1,2-propanediol is then added dropwise to the mixed solid-liquid, stirred evenly, to obtain a mixed liquid; the mixed liquid is heated to 40-50° C. for reaction for 12-20 hours, and then reacted at 60-70° C. for 1-2 hours, and the methanol solvent is removed to obtain a solid; the solid is vacuum dried for 24 hours to obtain a small molecule curing agent.

[0020] The synthesis principle of small molecule curing agent is as follows:

[0021]

[0022] Furthermore, the usage ratio of methanol, anhydrous magnesium sulfate, 3-aminophenylboric acid and 3-amino-1,2-propylene glycol is 50 mL:5 g:15-17 g:15 g.

[0023] Further, the modified inorganic filler is prepared by the following steps:

[0024] A1. Ultrasonic cleaning, drying and grinding of metal foam to 300-500 mesh with hydrochloric acid solution and deionized water in sequence to obtain dried metal foam; mixing aluminum powder with an average particle size of 30 μm and SiC micropowder with an average particle size of 20 μm, and ball milling in a ball mill, while passing argon gas for protection, to obtain an inorganic filler;

[0025] A2. The pretreated metal foam, inorganic filler and 0.3-0.5 mol / L dopamine hydrochloride solution are mixed evenly, allowed to stand for reaction, and then blown and dried under nitrogen to obtain a modified inorganic filler.

[0026] Metal foam has the advantages of stable chemical properties, large surface area and high porosity. The present invention wraps inorganic fillers in the outer layer of the metal foam to prepare a three-dimensional thermal conductive network, which effectively improves the thermal conductivity of the polymer composite material; however, since the surface of the metal foam is relatively smooth, it is not conducive to the inorganic filler to adhere to the surface of the metal foam. In order to improve the bonding strength between the inorganic filler and the metal foam, the surface of the metal foam must be appropriately modified. The present invention dips a hydrochloric acid polydopamine solution on the surface of the metal foam to improve the bonding strength between the inorganic filler and the metal foam.

[0027] Furthermore, in step A1, the metal foam is any one of metal foam copper, metal foam nickel or metal foam iron; the frequency of ultrasonic cleaning is 20KHz, and the duration of ultrasonic cleaning is 5-10min; the drying temperature is 60°C, and the drying time is 30min; in terms of weight parts, the amount ratio of aluminum powder and SiC micropowder is 1:1; the ball milling speed is 50-100r / min, and the ball-to-material ratio is 20:1; in step A2, the amount ratio of the pretreated metal foam, inorganic filler and dopamine hydrochloride solution is 5-10g:5g:30mL; the drying temperature is 60°C, and the drying time is 100-120min.

[0028] Further, in step S4, the leveling agent is BYK-425; the dispersant is BASF water-based dispersant; the defoaming agent is a silicone defoaming agent; in parts by weight, the amount ratio of the composite modified resin, the small molecule curing agent, the modified inorganic filler, the leveling agent, the dispersant and the defoaming agent is 60-70:2-3:10-20:1-2:0.5-1:0.5-1; during melt extrusion, the temperature of the first zone of the twin-screw extruder is 80-85°C, and the temperature of the second zone is 95-100°C.

[0029] Furthermore, the surface pretreated sheet metal bracket is prepared by the following steps:

[0030] The sheet metal bracket is ground with a grinding wheel at a speed of 10-30m / s for 3-5min to obtain a flattened sheet metal bracket; the flattened sheet metal bracket is deoiled with 20-30g / L NaOH for 5-10min to obtain a deoiled sheet metal bracket; and the deoiled sheet metal bracket is acid-soaked with 0.1mol / L hydrochloric acid for 2-3min to obtain a surface pretreated sheet metal bracket.

[0031] Furthermore, a wear-resistant and corrosion-resistant high-strength automobile sheet metal bracket is prepared by the following steps:

[0032] The surface pre-treated sheet metal bracket is electrostatically sprayed with wear-resistant and anti-corrosion coating to prepare a wear-resistant and corrosion-resistant high-strength automobile sheet metal bracket; wherein the voltage of the electrostatic spraying is 50-60kV, the current is 1-10mA, the distance between the spray gun and the sample is 10-20cm, and the spray film thickness is 70-80μm; the curing temperature is 140-150℃, and the curing time is 30min.

[0033] The purpose of surface leveling is to remove burrs, rust, scratches, sand holes, oxide scale and other macro defects on the surface of sheet metal bracket materials, thereby improving the surface flatness of sheet metal bracket materials. The purpose of alkaline solution degreasing is to remove grease on the surface of sheet metal bracket materials to avoid the reduction of the bonding strength between the surface coating and the substrate. Acid immersion rust removal refers to the removal of oxide scale or rust on the metal surface, and then the metal surface is etched and activated to reveal the crystalline structure of the sheet metal bracket metal to ensure a firm bond between the coating and the substrate. The present invention pre-treats the surface of the automobile sheet metal bracket, and then electrostatically sprays a wear-resistant and anti-corrosion coating on the surface to change the chemical composition, organizational structure and stress condition of the solid metal surface.

[0034] The present invention has the following beneficial effects:

[0035] 1. The present invention is to perform pre-treatment of grinding, alkaline liquid degreasing and acid immersion on the sheet metal bracket, so as to improve the bonding force between the sheet metal bracket and the wear-resistant and anti-corrosion coating. The wear-resistant and anti-corrosion coating prepared in the present invention specifically includes a composite modified resin, a small molecule curing agent, a modified inorganic filler and related additives. The composite modified resin includes a polyurethane prepolymer and an epoxy resin with a self-designed soft segment chain and a hard segment chain. On the one hand, the polyurethane prepolymer uses organic liquid silanol and tannic acid as the soft segment chain and diisocyanate as the hard segment chain, and introduces silicon elements and polyphenyl ring structures to improve the corrosion resistance of the polyurethane prepolymer; on the other hand, the polyurethane and prepolymer are compounded with epoxy resin to obtain a polyurethane / epoxy resin interpenetrating network, which significantly improves the mechanical properties of the prepared composite modified resin; in addition, the polyimino groups in the organic liquid silanol and the polyhydroxyl functional groups in the tannic acid can undergo cross-linking reactions with the isocyanate groups in the isocyanate, thereby improving the cross-linking network density of the prepared polyurethane prepolymer and further improving its own mechanical properties.

[0036] 2. Composite modified resins will inevitably produce defects due to collision or friction in daily use. In order to extend the service life of the above-mentioned composite modified resin, the present invention selects a curing agent containing a dynamic covalent borate bond. The polymer network containing the borate bond has dynamic reversibility. When subjected to external force, the polymer molecular chain is destroyed, but due to the external response, dynamic bond exchange occurs. The rapid exchange of dynamic bonds can promote chemical repair of broken chain segments.

[0037] 3. Modified inorganic fillers are added to the wear-resistant and anti-corrosion coating to improve the strength of the wear-resistant and anti-corrosion coating. Metal foam has the advantages of stable chemical properties, large surface area and high porosity. The present invention wraps the inorganic filler in the outer layer of the metal foam, thereby effectively improving the wear resistance of the wear-resistant and anti-corrosion coating. However, since the surface of the metal foam is relatively smooth, it is not conducive to the attachment of the inorganic filler to the surface of the metal foam. The present invention dips the surface of the metal foam with a polydopamine solution to improve the bonding force between the modified inorganic filler and the metal foam. In addition, the amino group in the polydopamine solution can react with the epoxy resin, thereby improving the bonding force between the modified inorganic filler and other components of the wear-resistant and anti-corrosion coating. DETAILED DESCRIPTION

[0038] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] Example 1

[0040] This embodiment provides a method for preparing a composite modified resin, comprising the following steps:

[0041] 1. Mix 25 mL of diethylenetriaminopropyltrimethoxysilane and 100 mL of deionized water, stir at 100 r / min for 30 min to obtain a mixed solution; heat the mixed solution to 100° C. and react until the volume of the mixed solution remains unchanged to obtain an organic liquid silanol.

[0042] 2. Add 5 mL of organic liquid silanol, 17 g of tannic acid and 100 mL of deionized water into a three-necked flask and mix them evenly to obtain a mixed solution; an electric heating jacket is arranged at the outer end of the three-necked flask, one end is connected to a vacuum pump and the other end is connected to a separating funnel, and the temperature of the three-necked flask is heated to 110° C. and reacted for 1 hour. During the reaction, a vacuum pump is used to remove the water produced by the reaction; the three-necked flask is cooled to room temperature, and then toluene diisocyanate (R (NCO / OH) value = 1.05) is added dropwise to the three-necked flask through a separating funnel. After the addition is completed, the temperature of the three-necked flask is heated to 60° C. and reacted at this temperature for 30 minutes, and then the temperature of the three-necked flask is heated to 80° C. and reacted at this temperature for 2 hours. After the reaction is completed, heating is stopped to obtain a polyurethane prepolymer.

[0043] 3. According to parts by weight, 30 parts of polyurethane prepolymer and 60 parts of epoxy resin are mixed to obtain a composite modified resin.

[0044] Example 2

[0045] This embodiment provides a method for preparing a composite modified resin, comprising the following steps:

[0046] 1. Mix 30 mL of diethylenetriaminopropyltrimethoxysilane and 100 mL of deionized water, stir at 100 r / min for 50 min to obtain a mixed solution; heat the mixed solution to 104°C, and react until the volume of the mixed solution remains unchanged to obtain an organic liquid silanol.

[0047] 2. Add 6 mL of organic liquid silanol, 25 g of tannic acid and 100 mL of deionized water into a three-necked flask and mix them evenly to obtain a mixed solution; an electric heating jacket is arranged at the outer end of the three-necked flask, one end is connected to a vacuum pump and the other end is connected to a separating funnel, and the temperature of the three-necked flask is heated to 114° C. and reacted for 1 hour. During the reaction, a vacuum pump is used to remove water produced by the reaction; the three-necked flask is cooled to room temperature, and then isophorone diisocyanate (R (NCO / OH) value = 1.05) is added dropwise to the three-necked flask through a separating funnel. After the addition is completed, the temperature of the three-necked flask is heated to 66° C. and reacted at this temperature for 50 minutes, and then the temperature of the three-necked flask is heated to 90° C. and reacted at this temperature for 2.2 hours. After the reaction is completed, heating is stopped to obtain a polyurethane prepolymer.

[0048] 3. According to parts by weight, 30 parts of polyurethane prepolymer and 62 parts of epoxy resin were mixed to obtain a composite modified resin.

[0049] Example 3

[0050] This embodiment provides a method for preparing a composite modified resin, comprising the following steps:

[0051] 1. Mix 35 mL of diethylenetriaminopropyltrimethoxysilane and 100 mL of deionized water, stir at 100 r / min for 60 min to obtain a mixed solution; heat the mixed solution to 110° C. and react until the volume of the mixed solution remains unchanged to obtain an organic liquid silanol.

[0052] 2. Add 10 mL of organic liquid silanol, 34 g of tannic acid and 100 mL of deionized water into a three-necked flask and mix well to obtain a mixed solution; an electric heating jacket is arranged at the outer end of the three-necked flask, one end is connected to a vacuum pump and the other end is connected to a separating funnel, and the temperature of the three-necked flask is heated to 120° C. and reacted for 1 hour. During the reaction, a vacuum pump is used to remove water generated during the reaction; the three-necked flask is cooled to room temperature, and then hexamethylene diisocyanate (R (NCO / OH) value = 1.05) is added dropwise to the three-necked flask through a separating funnel. After the addition is completed, the temperature of the three-necked flask is heated to 70° C. and reacted at this temperature for 60 minutes, and then the temperature of the three-necked flask is heated to 100° C. and reacted at this temperature for 2.5 hours. After the reaction is completed, heating is stopped to obtain a polyurethane prepolymer.

[0053] 3. According to parts by weight, 30 parts of polyurethane prepolymer and 70 parts of epoxy resin are mixed to obtain a composite modified resin.

[0054] Example 4

[0055] This embodiment provides a method for preparing a wear-resistant and anti-corrosion coating, comprising the following steps:

[0056] 1. Preparation of small molecule curing agent

[0057] In a 250mL three-necked flask, 50mL of methanol solvent, 5g of anhydrous magnesium sulfate and 13g of 3-aminophenylboric acid were added and mixed evenly to obtain a mixed solid-liquid A; a stirring bar was then set inside the three-necked flask, and a dropping funnel was connected to the flask mouth, and 15g of 3-amino-1,2-propanediol was dripped into the three-necked flask through the dropping funnel. During the dropping process, the mixture was stirred evenly at 100r / min to obtain a mixed solid-liquid B; the three-necked flask was transferred to a water bath, heated to 40°C for reaction for 20h, and then reacted at 60°C for 2h to remove the methanol solvent to obtain a solid; the solid was placed in a vacuum oven and dried at 70°C for 24h to obtain a small molecule curing agent.

[0058] 2. Preparation of modified inorganic fillers

[0059] The metal foam copper was ultrasonically cleaned with 0.1 mol / L hydrochloric acid solution and deionized water in sequence, with a solid-liquid ratio of 1:2, an ultrasonic cleaning time of 5 minutes, and an ultrasonic cleaning frequency of 20 KHz, and then placed in a drying oven for drying at 60°C for 30 minutes to obtain a dried metal foam; aluminum powder with an average particle size of 30 μm and SiC micropowder with an average particle size of 20 μm were mixed in a mass ratio of 1:1, and then placed in a cylindrical ball mill for mechanical dispersion, and argon gas was introduced for protection during ball milling to obtain an inorganic filler; wherein the ball milling speed was 50 r / min and the ball-to-material ratio was 20:1.

[0060] 5 g of the pretreated metal foam, 5 g of the inorganic filler and 30 mL of a 0.3 mol / L dopamine hydrochloride solution were mixed evenly, allowed to react for 30 min, then dried under nitrogen conditions, and dried in an oven at 60° C. for 100 min to obtain a modified inorganic filler.

[0061] 3. Preparation of wear-resistant and anti-corrosion coatings

[0062] According to parts by weight, 60 parts of the composite modified resin prepared in Example 1, 2 parts of a small molecule curing agent, 10 parts of a modified inorganic filler, 1 part of a BYK-425 leveling agent, 0.5 parts of a BASF aqueous dispersant and 0.5 parts of a silicone defoaming agent were mixed uniformly to obtain a mixture; the mixture was cured at 120° C. for 30 min, and then added to a twin-screw extruder for extrusion, wherein the temperature of the first zone was 80° C. and the temperature of the second zone was 95° C., and then cooled, crushed, and passed through a 200-mesh sieve to obtain a wear-resistant and anti-corrosion coating.

[0063] Example 5

[0064] This embodiment provides a method for preparing a wear-resistant and anti-corrosion coating, comprising the following steps:

[0065] 1. Preparation of small molecule curing agent

[0066] Add 50 mL of methanol solvent, 5 g of anhydrous magnesium sulfate and 15 g of 3-aminophenylboronic acid into a 250 mL three-necked flask and mix well to obtain a mixed solid-liquid A. Then, set a stirrer inside the three-necked flask, connect a dropping funnel to the flask mouth, and drop 15 g of 3-amino-1,2-propanediol into the three-necked flask through the dropping funnel. Stir well at 100 r / min during the dropping process to obtain a mixed solid-liquid B. Transfer the three-necked flask to a water bath, heat to 45 ° C for 15 h, and then react at 66 ° C for 1.5 h, remove the methanol solvent, and obtain a solid. Place the solid in a vacuum oven and dry it at 70 ° C for 24 h to obtain a small molecule curing agent.

[0067] 2. Preparation of modified inorganic fillers

[0068] The metal foam nickel was ultrasonically cleaned with 0.1 mol / L hydrochloric acid solution and deionized water in sequence, with a solid-liquid ratio of 1:2, an ultrasonic cleaning time of 7 minutes, and an ultrasonic cleaning frequency of 20 KHz, and then placed in a drying oven for drying at 60°C for 30 minutes to obtain a dried metal foam; aluminum powder with an average particle size of 30 μm and SiC micropowder with an average particle size of 20 μm were mixed in a mass ratio of 1:1, and then placed in a cylindrical ball mill for mechanical dispersion treatment, and argon gas was introduced for protection during ball milling to obtain an inorganic filler; wherein the ball milling speed was 80 r / min and the ball-to-material ratio was 20:1.

[0069] 7 g of the pretreated metal foam, 5 g of the inorganic filler and 30 mL of a 0.4 mol / L dopamine hydrochloride solution were mixed evenly, allowed to react for 30 min, then dried under nitrogen, and dried in an oven at 60° C. for 110 min to obtain a modified inorganic filler.

[0070] 4. Preparation of wear-resistant and anti-corrosion coatings

[0071] According to weight parts, 65 parts of the composite modified resin prepared in Example 2, 2 parts of small molecule curing agent, 15 parts of modified inorganic filler, 1 part of BYK-425 leveling agent, 0.1 part of BASF water-based dispersant and 0.5 parts of silicone defoaming agent were mixed uniformly to obtain a mixture; the mixture was cured at 130°C for 25 minutes, and then added to a twin-screw extruder for extrusion, wherein the temperature of zone 1 was 82°C and the temperature of zone 2 was 98°C, and then cooled, crushed, and passed through a 400-mesh sieve to obtain a wear-resistant and anti-corrosion coating.

[0072] Example 6

[0073] This embodiment provides a method for preparing a wear-resistant and anti-corrosion coating, comprising the following steps:

[0074] 1. Preparation of small molecule curing agent

[0075] Add 50 mL of methanol solvent, 5 g of anhydrous magnesium sulfate and 17 g of 3-aminophenylboronic acid into a 250 mL three-necked flask and mix well to obtain a mixed solid-liquid A. Then, set a stirrer inside the three-necked flask, connect a dropping funnel to the flask mouth, and drop 15 g of 3-amino-1,2-propanediol into the three-necked flask through the dropping funnel. Stir well at 100 r / min during the dropping process to obtain a mixed solid-liquid B. Transfer the three-necked flask to a water bath, heat to 50 ° C for 12 h, and then react at 70 ° C for 1 h to remove the methanol solvent to obtain a solid. Place the solid in a vacuum oven and dry it at 70 ° C for 24 h to obtain a small molecule curing agent.

[0076] 2. Preparation of modified inorganic fillers

[0077] The metal foam iron is ultrasonically cleaned with 0.1 mol / L hydrochloric acid solution and deionized water in sequence, with a solid-liquid ratio of 1:3, an ultrasonic cleaning time of 10 min, and an ultrasonic cleaning frequency of 20 KHz, and then placed in a drying oven for drying at 60° C. for 30 min to obtain a dried metal foam; aluminum powder with an average particle size of 30 μm and SiC micropowder with an average particle size of 20 μm are mixed in a mass ratio of 1:1, and then placed in a cylindrical ball mill for mechanical dispersion treatment, and argon gas is introduced for protection during ball milling to obtain an inorganic filler; wherein the ball milling speed is 100 r / min and the ball-to-material ratio is 20:1.

[0078] 10 g of the pretreated metal foam, 5 g of the inorganic filler and 30 mL of a 0.5 mol / L dopamine hydrochloride solution were mixed evenly, allowed to react for 30 min, then dried under nitrogen, and dried in an oven at 60° C. for 120 min to obtain a modified inorganic filler.

[0079] 3. Preparation of wear-resistant and anti-corrosion coatings

[0080] According to weight parts, 70 parts of the composite modified resin prepared in Example 3, 3 parts of small molecule curing agent, 20 parts of modified inorganic filler, 2 parts of BYK-425 leveling agent, 1 part of BASF water-based dispersant and 1 part of silicone defoaming agent were mixed uniformly to obtain a mixture; the mixture was cured at 140°C for 20 minutes, and then added to a twin-screw extruder for extrusion, wherein the temperature of zone 1 was 85°C and the temperature of zone 2 was 100°C, and then cooled, crushed, and passed through a 500-mesh sieve to obtain a wear-resistant and anti-corrosion coating.

[0081] Example 7

[0082] This embodiment provides a wear-resistant and corrosion-resistant high-strength automobile sheet metal bracket, comprising the following steps:

[0083] S1. The surface of the sheet metal bracket is ground with an aluminum oxide grinding wheel at a speed of 10 m / s for 5 minutes to obtain a flattened sheet metal bracket; the flattened sheet metal bracket is deoiled with 20 g / L NaOH for 10 minutes to obtain a deoiled sheet metal bracket; the deoiled sheet metal bracket is then acid-soaked with 0.1 mol / L hydrochloric acid for 3 minutes to obtain a surface pretreated sheet metal bracket.

[0084] S2. Spray the wear-resistant and anti-corrosion coating prepared in Example 4 onto the surface of the sheet metal bracket to obtain a sprayed sheet metal bracket; wherein the voltage of the electrostatic spraying is 50 kV, the current is 1 mA, the distance between the spray gun and the sample is 10 cm, and the spray film thickness is 70 μm. The sprayed sheet metal bracket is placed in an oven at 140° C. for curing for 30 minutes to obtain a wear-resistant and corrosion-resistant high-strength sheet metal bracket.

[0085] Example 8

[0086] This embodiment provides a wear-resistant and corrosion-resistant high-strength automobile sheet metal bracket, comprising the following steps:

[0087] S1. The surface of the sheet metal bracket is ground with an aluminum oxide grinding wheel at a speed of 20 m / s for 5 minutes to obtain a flattened sheet metal bracket; the flattened sheet metal bracket is deoiled with 25 g / L NaOH for 6 minutes to obtain a deoiled sheet metal bracket; the deoiled sheet metal bracket is then acid-soaked with 0.1 mol / L hydrochloric acid for 3 minutes to obtain a surface pretreated sheet metal bracket.

[0088] S2. Spray the wear-resistant and anti-corrosion coating prepared in Example 5 onto the surface of the sheet metal bracket to obtain a sprayed sheet metal bracket; wherein the voltage of the electrostatic spraying is 55 kV, the current is 6 mA, the distance between the spray gun and the sample is 15 cm, and the spray film thickness is 75 μm. The sprayed sheet metal bracket is placed in an oven at 144° C. for curing for 30 minutes to obtain a wear-resistant and corrosion-resistant high-strength sheet metal bracket.

[0089] Example 9

[0090] This embodiment provides a wear-resistant and corrosion-resistant high-strength automobile sheet metal bracket, comprising the following steps:

[0091] S1. The surface of the sheet metal bracket is ground with an aluminum oxide grinding wheel at a speed of 30 m / s for 5 minutes to obtain a flattened sheet metal bracket; the flattened sheet metal bracket is deoiled with 30 g / L NaOH for 5 minutes to obtain a deoiled sheet metal bracket; the deoiled sheet metal bracket is then acid-soaked with 0.1 mol / L hydrochloric acid for 2 minutes to obtain a surface pretreated sheet metal bracket.

[0092] S2. Spray the wear-resistant and anti-corrosion coating prepared in Example 6 onto the surface of the sheet metal bracket to obtain a sprayed sheet metal bracket; wherein the voltage of the electrostatic spraying is 60 kV, the current is 10 mA, the distance between the spray gun and the sample is 20 cm, and the spraying film thickness is 80 μm. The sprayed sheet metal bracket is placed in an oven at 150° C. for curing for 30 minutes to obtain a wear-resistant and corrosion-resistant high-strength sheet metal bracket.

[0093] Comparative Example 1

[0094] Compared with the wear-resistant and corrosion-resistant high-strength automobile sheet metal bracket prepared in Example 9, no modified inorganic filler is added to the sprayed wear-resistant and anti-corrosion coating in this comparative example.

[0095] Comparative Example 2

[0096] Compared with the wear-resistant and corrosion-resistant high-strength automobile sheet metal bracket prepared in Example 9, in the sprayed wear-resistant and anti-corrosion coating, compared with Example 3, no tannic acid was added when preparing the polyurethane prepolymer.

[0097] Comparative Example 3

[0098] Compared with the wear-resistant and corrosion-resistant high-strength automobile sheet metal bracket prepared in Example 9, in the sprayed wear-resistant and anti-corrosion coating, compared with Example 3, no polyurethane prepolymer was added when preparing the composite modified resin.

[0099] Performance Testing:

[0100] 1. According to GB / T1768 "Determination of Wear Resistance of Paints and Varnishes - Rotating Rubber Grinding Wheel Method", the wear resistance of the wear-resistant and corrosion-resistant high-strength sheet metal brackets of Examples 7-9 and Comparative Examples 1-3 was tested, wherein the rotation speed of the wear meter was 60r / min, the load was 500g, and the number of revolutions was 500r. An analytical balance was used to measure the coating quality before and after wear, and the quality difference before and after was calculated as the test data. Examples 1-3 and Comparative Examples 1-3 were measured 3 times and the average value was taken as the test result.

[0101] 2. The wear-resistant and corrosion-resistant high-strength sheet metal brackets prepared in Examples 7-9 and Comparative Examples 1-3 were placed in a refrigerator at a constant temperature of -15°C for a low-temperature aging test. The wear-resistant and corrosion-resistant high-strength sheet metal brackets prepared in Examples 7-9 and Comparative Examples 1-3 were placed in an environment with a temperature of 60°C and a relative humidity of 90 for a constant temperature and humidity aging test. The wear-resistant and corrosion-resistant high-strength sheet metal brackets prepared in Examples 7-9 and Comparative Examples 1-3 were placed in an environment with ultraviolet light for an ultraviolet aging test. The wear-resistant and corrosion-resistant high-strength sheet metal brackets prepared in Examples 7-9 and Comparative Examples 1-3 were placed in a constant temperature of 90°C, 3.5wt% NaCl solution for a constant temperature salt water immersion aging test, wherein the number of cycles was 3 times.

[0102] 3. Determine the Shore hardness of the surface coating of the wear-resistant and corrosion-resistant high-strength sheet metal brackets prepared in Examples 7-9 and Comparative Examples 1-3, wherein the hardness tester needle is perpendicular to the surface of the high-strength sheet metal bracket, and the same position is tested five times with a distance between points of 6 mm, and the average value is used as the hardness data.

[0103] The specific test results are shown in the table below:

[0104] Table 1

[0105]

[0106] Data Analysis:

[0107] The wear-resistant and corrosion-resistant high-strength automobile sheet metal brackets prepared in Examples 7-9 all have good wear resistance, Shore hardness, and aging and corrosion resistance. However, in Comparative Example 1, no modified inorganic filler was added to the wear-resistant and anti-corrosion coating sprayed on the automobile sheet metal bracket, which significantly reduced its own wear resistance and hardness. In Comparative Example 2, no tannic acid was added when preparing the wear-resistant and anti-corrosion coating. In Comparative Example 3, no polyurethane prepolymer was added when preparing the composite modified resin, which significantly reduced its own aging resistance.

[0108] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

[0109] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0110] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A wear-resistant and corrosion-resistant high-strength automobile sheet metal bracket, comprising a sheet metal bracket and a wear-resistant and corrosion-resistant coating coated on the outside of the sheet metal bracket, characterized in that: The wear-resistant and anti-corrosion coating is obtained by spraying the wear-resistant and anti-corrosion coating on the outside of the surface pre-treated sheet metal bracket and then curing and forming; The wear-resistant and anti-corrosion coating is obtained by processing the following steps: S1, diethylenetriaminopropyltrimethoxysilane and deionized water are mixed and stirred to obtain a mixed solution; the mixed solution is heated to 100-110° C. and reacted until the volume of the mixed solution remains unchanged to obtain an organic liquid silanol; S2, mixing organic liquid silanol, tannic acid and deionized water uniformly to obtain a mixed solution; heating the mixed solution to 110-120°C and reacting for 1-2h, using a vacuum pump to remove water during the reaction, then cooling the mixed solution to room temperature, and then dropping diisocyanate into the mixed solution. After the dropping is complete, heating it to 60-70°C, reacting for 30-60min, and then heating it to 80°C, reacting for 2-2.5h. After the reaction is completed, stopping heating to obtain a polyurethane prepolymer; S3, according to weight parts, 30 parts of polyurethane prepolymer and 60-70 parts of epoxy resin are mixed uniformly to obtain a composite modified resin; S4, the composite modified resin, small molecule curing agent, modified inorganic filler, leveling agent, dispersant and defoaming agent are mixed uniformly to obtain a mixture; the mixture is cured at 120-140° C. for 20-30 min, then melt-extruded, cooled, crushed, and sieved to obtain a wear-resistant and anti-corrosion coating, wherein the amount ratio of the composite modified resin, small molecule curing agent, modified inorganic filler, leveling agent, dispersant and defoaming agent is 60-70:2-3:10-20:1-2:0.5-1:0.5-1 according to weight parts; The small molecule curing agent is prepared by the following steps: Methanol, anhydrous magnesium sulfate and 3-aminophenylboric acid are mixed evenly to obtain a mixed solid-liquid A; 3-amino-1,2-propanediol is then added dropwise to the mixed solid-liquid A and stirred evenly to obtain a mixed solid-liquid B; the mixed solid-liquid B is heated to 40-50°C for reaction for 12-20h, and then reacted at 60-70°C for 1-2h, and the methanol solvent is removed to obtain a solid; the solid is vacuum dried for 24h to obtain a small molecule curing agent, wherein the amount ratio of methanol, anhydrous magnesium sulfate, 3-aminophenylboric acid and 3-amino-1,2-propanediol is 50mL:5g:13-17g:15g; The modified inorganic filler is prepared by the following steps: A1. Ultrasonic cleaning, drying and grinding of metal foam to 300-500 mesh with hydrochloric acid solution and deionized water in sequence to obtain dried metal foam; mixing aluminum powder with an average particle size of 30 μm and SiC micropowder with an average particle size of 20 μm, and ball milling in a ball mill, while introducing argon gas protection during ball milling to obtain an inorganic filler, wherein the amount ratio of aluminum powder to SiC micropowder is 1:1 in parts by weight; A2. The pretreated metal foam, inorganic filler and 0.3-0.5 mol / L dopamine hydrochloride solution are mixed evenly, allowed to stand for reaction, and then blown and dried under nitrogen conditions to obtain a modified inorganic filler, wherein the amount ratio of the pretreated metal foam, inorganic filler and dopamine hydrochloride solution is 5-10 g:5 g:30 mL.

2. The wear-resistant and corrosion-resistant high-strength automobile sheet metal bracket according to claim 1, characterized in that: In step S1, the dosage ratio of diethylenetriaminopropyltrimethoxysilane and deionized water is 25-35mL:100mL; the mixing speed is 100r / min, and the mixing time is 30-60min.

3. The wear-resistant and corrosion-resistant high-strength automobile sheet metal bracket according to claim 1, characterized in that: In step S2, the diisocyanate is any one of toluene diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, and p-phenylene diisocyanate, and a combination thereof; in step S3, the epoxy resin is bisphenol A epoxy resin.

4. The wear-resistant and corrosion-resistant high-strength automobile sheet metal bracket according to claim 1, characterized in that: In step A1, the metal foam is any one of metal foam copper, metal foam nickel or metal foam iron; the frequency of ultrasonic cleaning is 20KHz, and the duration of ultrasonic cleaning is 5-10min; the drying temperature is 60°C, and the drying time is 30min; the ball milling speed is 50-100r / min, and the ball-to-material ratio is 20:1; in step A2, the drying temperature is 60°C, and the drying time is 100-120min.

5. The wear-resistant and corrosion-resistant high-strength automobile sheet metal bracket according to claim 1, characterized in that: In step S4, the leveling agent is BYK-425 leveling agent; the dispersant is BASF water-based dispersant; the defoaming agent is a silicone defoaming agent; during melt extrusion, the temperature of the first zone of the twin-screw extruder is 80-85° C., and the temperature of the second zone is 95-100° C.

6. The wear-resistant and corrosion-resistant high-strength automobile sheet metal bracket according to claim 1, characterized in that: The surface pretreated sheet metal bracket is prepared by the following steps: The sheet metal bracket is ground with a grinding wheel at a speed of 10-30m / s for 3-5min to obtain a flattened sheet metal bracket; the flattened sheet metal bracket is deoiled with 20-30g / L NaOH for 5-10min to obtain a deoiled sheet metal bracket; and the deoiled sheet metal bracket is acid-soaked with 0.1mol / L hydrochloric acid for 2-3min to obtain a surface pretreated sheet metal bracket.

7. The wear-resistant and corrosion-resistant high-strength automobile sheet metal bracket according to claim 1, characterized in that: Prepared by the following steps: The surface pre-treated sheet metal bracket is electrostatically sprayed with wear-resistant and anti-corrosion coating to prepare a wear-resistant and corrosion-resistant high-strength automobile sheet metal bracket; wherein the voltage of the electrostatic spraying is 50-60kV, the current is 1-10mA, the distance between the spray gun and the sample is 10-20cm, and the spray film thickness is 70-80μm; the curing temperature is 140-150℃, and the curing time is 30min.

Citation Information

Patent Citations

  • Anticorrosion wear-resistant powdery paint

    CN103497552A

  • UV digital printing based surface photocuring coating for treating metal material for sheet-metal working

    CN105925149A

  • Coated metal plate having excellent conductivity and corrosion resistance

    CN103180136A

  • Three-dimensional network porous heat-conducting heat radiation device and preparation method thereof

    CN107936777A

  • Hydrophobic coating for anti-wall-hanging container barrel and preparation method of hydrophobic coating

    CN114656877A